Pendampingan Optimalisasi Penggunaan E-Commerce dalam Pemasaran Batik Khas untuk Meningkatkan Omzet UMKM di Desa Tampaksiring, Kabupaten Gianyar, Provinsi Bali - Purmiyati, Atik; Rahmawati, Ely (Universitas Medan Area, 2024)
Tampaksiring Village has great potential in the Micro, Small and Medium Enterprises (MSMEs) sector, especially in the field of batik crafts. Although many batik entrepreneurs have high motivation to develop and compete globally, the main obstacle faced is the lack of effective marketing strategies, which results in a minimal product market share. Therefore, training and mentoring are needed for the community to increase economic potential and achieve Sustainable Development Goals (SDGs). This study aims to analyze weaknesses and strengths in the economic sector using SWOT analysis techniques. The calculation of the Internal Factor Index (IFAS) and External Factor Index (EFAS) places it in quadrant 1, indicating that its strengths are more dominant than its weaknesses. In addition, quadrant 4 indicates that the opportunities faced outweigh the threats faced. Therefore, measures are needed to maintain the position in quadrant 1 by increasing strengths and reducing weaknesses. The recommended strategy based on the SWOT Analysis is to maximize the potential of human resources in marketing typical processed products. Steps that can be taken by the community to increase turnover include creating websites and utilizing social networks as promotional media, cooperation with business partners, the use of modern technology, expanding promotional networks, and seeking support from the government.